EFEKTIVITAS STRATEGI SCAFFOLDING METAKOGNITIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI SPLTV MELALUI SLR - Tatu Ambarwati; Maman Fathurrohman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Students’ mathematical problem-solving ability in the topic of the System of Linear Equations in Three Variables (SPLTV) remains a challenge, as students often experience difficulties in understanding concepts and solving problems in a systematic way. This study aims to analyze the effectiveness of metacognitive scaffolding strategies in improving students’ systematic problem-solving skills in SPLTV. The research method used is a Systematic Literature Review (SLR) by analyzing 15 scientific articles obtained from databases such as Google Scholar, ScienceDirect, ERIC, and journals indexed in SINTA and Scopus. The article selection process was conducted through several stages, namely identification, screening, eligibility assessment, and final inclusion based on predefined inclusion and exclusion criteria. The results show that metacognitive scaffolding plays a role in providing step-by-step assistance that helps students understand concepts, plan solution strategies, and evaluate their problem-solving processes. In addition, the integration of scaffolding and metacognitive strategies is proven to be more effective than the use of each strategy separately in improving students’ mathematical problem-solving abilities in SPLTV. Therefore, metacognitive scaffolding can be considered an effective instructional approach to enhance students’ systematic thinking skills in mathematics learning ABSTRAK Kemampuan pemecahan masalah matematis siswa pada materi Sistem Persamaan Linear Tiga Variabel (SPLTV) masih menjadi tantangan karena siswa cenderung mengalami kesulitan dalam memahami konsep dan menyelesaikan masalah secara sistematis. Penelitian ini bertujuan untuk menganalisis efektivitas strategi scaffolding metakognitif dalam meningkatkan kemampuan pemecahan masalah sistematis siswa pada materi SPLTV. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan menganalisis 15 artikel ilmiah yang diperoleh dari database Google Scholar, ScienceDirect, ERIC, serta jurnal terindeks SINTA dan Scopus. Proses seleksi artikel dilakukan melalui tahapan identifikasi, screening, eligibility, dan penentuan artikel akhir berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Hasil penelitian menunjukkan bahwa strategi scaffolding metakognitif berperan dalam memberikan bantuan bertahap yang membantu siswa memahami konsep, merencanakan penyelesaian, serta mengevaluasi proses pemecahan masalah. Selain itu, integrasi scaffolding dan strategi metakognitif terbukti lebih efektif dibandingkan penggunaan masing-masing strategi secara terpisah dalam meningkatkan kemampuan pemecahan masalah matematis siswa pada materi SPLTV. Dengan demikian, scaffolding metakognitif dapat dijadikan sebagai pendekatan pembelajaran yang efektif untuk meningkatkan kemampuan berpikir sistematis siswa dalam pembelajaran matematika